An Acute Bout of Self-Myofascial Release Does Not Affect Drop Jump Performance despite an Increase in Ankle Range of Motion - Mark Godwin; Edward Stanhope; James Bateman; Holly Mills (MDPI AG, 2020)
This study examined the acute effects of self-myofascial release plus dynamic warm up versus dynamic warm up alone on ankle range of motion and drop jump performance. Twenty-five recreationally active participants (male: 16, female: 9) were randomly assigned into a foam rolling (FR) or a dynamic warm up group (CON) (age: 22.8 ± 3.9 years, body mass 75.9 ± 13.2 kg, stretch stature: 174.1 ± 10.1 cm). In a randomised crossover design, each participant completed two experimental sessions that were separated by seven days. Ankle range of movement was assessed while using a weight-bearing lunge test and drop jump performance was recorded via bilateral force plates. Following a 5 min cycle, the foam rolling group undertook self-myofascial release to the lower limb and thoracic/lumbar regions, followed by a dynamic warm up. The control group undertook the same initial warm up plus the dynamic exercises. The level of significance was set at p ≤ 0.05. There was a significant increase (p < 0.001) in ankle range of motion immediately after the warm up for both groups (pre CON: 37.5 ± 5.31, post CON: 39.8 ± 5.76; pre FR 38.7 ± 7, post FR: 40.3 ± 7.3 deg). No significant difference was found between the conditions (p > 0.05). There were no significant differences for any indices of jump performance (p > 0.05). Based on these results, foam rolling plus dynamic exercises does not appear to impair or enhance drop jump performance, despite the increases in ankle range of movement.